2014
DOI: 10.1109/jqe.2014.2351012
|View full text |Cite
|
Sign up to set email alerts
|

Induced Focusing of Optical Wave From Cross-Phase Modulation in Nonlinear Metamaterials

Abstract: In this paper, we investigate the novel behavior of induced focusing in nonlinear metamaterials (MMs) through designing probe-pump configuration, where the coupled waves may simultaneously experience negative refractive index or positive refractive index, or one experiences positive refractive index and another experiences negative refractive index both analytically and numerically. It is shown that cross-phase modulation (XPM) in MM not only brings some new features to the behavior of induced focusing, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Therefore, in our pioneer work, we have reported that transverse-XPM MI can develop for different combinations of the signs of refractive index decided by the two waves, respectively, which makes the temporal MI in optical fibers find the corresponding transverse case in MMs [31]. Meanwhile, we also disclose the new temporal MI properties induced by XPM in MM and identify the influence of group-velocity mismatch(GVM) on MI [32].Very recently, we further investigate the novel behavior of induced focusing in nonlinear MMs through designing probe-pump configuration both analytically and numerically [30]. In addition, Chen et al report that there exists single-and multi-peak soliton pairs from XPM in two-component models of MMs and photonic crystals [33].…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Therefore, in our pioneer work, we have reported that transverse-XPM MI can develop for different combinations of the signs of refractive index decided by the two waves, respectively, which makes the temporal MI in optical fibers find the corresponding transverse case in MMs [31]. Meanwhile, we also disclose the new temporal MI properties induced by XPM in MM and identify the influence of group-velocity mismatch(GVM) on MI [32].Very recently, we further investigate the novel behavior of induced focusing in nonlinear MMs through designing probe-pump configuration both analytically and numerically [30]. In addition, Chen et al report that there exists single-and multi-peak soliton pairs from XPM in two-component models of MMs and photonic crystals [33].…”
Section: Introductionmentioning
confidence: 87%
“…Very recently, advances in the fabrication of MMs, ranging from microwave to optical frequency and from linear to nonlinear effect, have further stimulated a great deal of research including the revaluation and characterization of the classical nonlinear optical processes [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Accordingly, the wide study of self-focusing phenomena in Kerr nonlinear NIM has recently become a new and exciting field of research that has been the subject of intense investigations [25][26][27][28][29][30][31]. Several intriguing and counterintuitive nonlinear phenomena associated with optical collapse, optical solitons as well as modulation instability (MI) have been substantially disclosed [24][25][26][27][28][29][30][31][32][33][34][35] due to the anomalous electromagnetic properties of such materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations